The impact of COVID-19 on primary health care and antibiotic prescribing in rural China: qualitative study - Tingting Zhang; Xingrong Shen; Rong Liu; Linhai Zhao; Debin Wang; Helen Lambert; Christie Cabral (BMC, 2021)
Abstract Background In China, the primary health care (PHC) system has been designated responsible for control and prevention of COVID-19, but not treatment. Suspected COVID-19 cases presenting to PHC facilities must be transferred to specialist fever clinics. This study aims to understand the impact of COVID-19 on PHC delivery and on antibiotic prescribing at a community level in rural areas of central China. Methods Qualitative semi-structured interviews were conducted with 18 PHC practitioners and seven patients recruited from two township health centres and nine village clinics in two rural residential areas of Anhui province. Interviews were transcribed verbatim and analysed thematically. Results PHC practitioners reported a major shift in their work away from seeing and treating patients (due to government-mandated referral to specialist Covid clinics) to focus on the key public health roles of tracing, screening and educating in rural areas. The additional work, risk, and financial pressure that PHC practitioners faced, placed considerable strain on them, particularly those working in village clinics. Face to face PHC provision was reduced and there was no substitution with consultations by phone or app, which practitioners attributed to the fact that most of their patients were elderly and not willing or able to switch. Practitioners saw COVID-19 as outside of their area of expertise and very different to the non-COVID-19 respiratory tract infections that they frequently treated pre-pandemic. They reported that antibiotic prescribing was reduced overall because far fewer patients were attending rural PHC facilities, but otherwise their antibiotic prescribing practices remained unchanged. Conclusions The COVID-19 pandemic had considerable impact on PHC in rural China. Practitioners took on substantial additional workload as part of epidemic control and fewer patients were seen in PHC. The reduction in patients seen and treated in PHC led to a reduction in antibiotic prescribing, although clinical practice remains unchanged. Since COVID-19 epidemic control work has been designated as a long-term task in China, rural PHC clinics now face the challenge of how to balance their principal clinical and increased public health roles and, in the case of the village clinics, remain financially viable.